Prinsip Teologis Memenangkan Suami yang Belum Percaya Berdasarkan 1 Petrus 3:1-6 - Sari Yuliani; Nidya Arvita Talumewo (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
The phenomenon of interfaith marriages between Christian wives and non-believing husbands poses complex challenges and problems for families in Indonesia. In the context of Indonesian culture, which is still strongly influenced by patriarchal patterns, an inaccurate interpretation of 1 Peter 3:16 has given rise to practices among Christian wives that are not in accordance with the intent of the Bible. Specifically, in interpreting the word “submission.” This study aims to analyze the phenomenon of interfaith marriages between Christian wives and unbelieving husbands in the context of Indonesian culture, which is still influenced by patriarchal patterns and modern feminist trends. Through a qualitative approach with an expository study of 1 Peter 3:1–6, this study aims to discover contextual and applicable theological principles in interpreting submission, so that it is not understood as restraint, but as a spiritual strategy that presents a complete testimony of life. The ultimate goal of this study is to provide a theological contribution while opening space for the development of pastoral and faith education models that can bridge the tension between patriarchal culture, the influence of feminism, and true biblical testimony.AbstrakFenomena pernikahan beda iman antara istri Kristen dan suami yang belum percaya menimbulkan tantangan dan masalah yang kompleks dalam keluarga di Indonesia. Dalam konteks budaya Indonesia yang masih kuat dipengaruhi pola patriarkhi, kemudian tafsir yang tidak tepat terhadap surat 1 Petrus 3:16 telah melahirkan praktik hidup istri Kristen yang tidak sesuai dengan maksud Alkitab. Secara khusus dalam memaknai kata tunduk. Penelitian ini bertujuan untuk menganalisis fenomena pernikahan beda iman antara istri Kristen dan suami yang belum percaya dalam konteks budaya Indonesia yang masih dipengaruhi pola patriarki serta arus feminisme modern. Melalui pendekatan kualitatif dengan studi eksposisi 1 Petrus 3:1–6, penelitian ini dimaksudkan untuk menemukan prinsip-prinsip teologis yang kontekstual dan aplikatif dalam memaknai ketundukan, sehingga tidak dipahami sebagai pengekangan, melainkan sebagai strategi rohani yang menghadirkan kesaksian hidup yang utuh. Tujuan akhir penelitian ini adalah memberikan kontribusi teologis sekaligus membuka ruang bagi pengembangan model pastoral dan pendidikan iman yang mampu menjembatani ketegangan antara budaya patriarki, pengaruh feminisme, dan kesaksian Alkitabiah yang sejati.